Dynamics of Coupled Structures, Volume 4 : Proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016 /: Proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016. (2016) - Unknown
No abstract available